The Use of Code-Mixing Among Jaksel People on Jagobahasa.com’s TikTok Account - Michelle Septia; Endar Rachmawaty Linuwih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
What this research explores is a sociolinguistic phenomenon using code mixing techniques between Indonesian and English, especially among teenagers in South Jakarta, to become a form of identity expression and adaptation to modern urban culture. Although there are various studies that discuss code mixing in digital contexts, limited research has examined how this linguistic practice influences the perception of a person's language and their emotional expression among speakers, especially on popular applications such as TikTok. This research uses sociolinguistic theory to analyze the Jagolingual account on the TikTok application and observation data from 3 videos to be able to describe identity. What was found in this research was about South Jakarta teenagers who used codemixing techniques by inserting English terms into their daily communication to be able to express what they felt, build their identity, and be able to better describe modern social values, which could indicate increased psychological literacy and also their adaptation to global culture. The conclusion of this research shows that South Jakarta teenagers use English codemixing to express feelings, form identity, and reflect social values as a form of adaptation to global culture.